PENDIDIKAN AGAMA ISLAM BAGI ANAK TUNAGRAHITA DI SEKOLAH LUAR BIASA YAYASAN PEMBINAAN ANAK CACAT SEMARANG - Sukijan Athoillah (AT-TAJDID, 2017)
This study aims to know and explain; 1) implementation of Islamic religious education for mental retardation children in Extraordinary school C YPAC Semarang; and 2) explain the implications of the implementation of Islamic religious education for mental retardation children in Extraordinary school C YPAC Semarang. This research is a qualitative research type of field research by taking the background of Special School C Foundation for Disabled Children Development Semarang. Mental retardation children are entitled to a religious education worthy in accordance with their respective religions. In this case, Muslim children are given Islamic religious education services to instill Islamic aqidah correctly. Implementation of Islamic education can provide a positive implication for the mental retardation childrens, they can better understand the theory and practice of Islamic religion well. With the knowledge he possesses, he will realize that Allah is Almighty to his creation, so that the mental retardation children are not protracted bemoaning their deficient circumstances. They can be well aware of the situation and can provide stability to the mental.